NESTING OF PEREGRINE FALCON ALONG THE SEASHORE OF THE ABRAU PENINSULA (KRASNODAR REGION) - Vladislav S. Rudovskiy (Вестник Северо-Кавказского федерального университета, 2022)
Thе article describes the modern distribution of Peregrine Falcon (Falco peregrinus) and some features of its nesting along the seashore of the Abrau peninsula in Krasnodar region.